DAMPAK KERJASAMA PENDIDIKAN INDONESIA DAN SINGAPURA (STUDI KASUS: SISTER SCHOOL SMA LABSCHOOL JAKARTA DAN CHIJ ST. JOSEPH’S CONVENT SINGAPURA 2008-2011) - Sitompul, Martahi Saoloan; Tjarsono, Idjang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Indonesia has the initiative to corporate with Singapore to improve the quality ofeducation in Indonesia. So, in 2005, the representatives from Indonesia and Singapore met todiscuss about cooperation between educational institution in Indonesia and Singapore. Someschools in Indonesia that have local advantages have been paired with schools in Singaporein a program that called Sister School.This cooperation has been ongoing since 2008 until2011.This is a qualitative research by using primer and secondary file. The writer collectdata from journals, books, reports, working papers and online media. This research usescooperation theory and neo liberalism perspective. The level analysis used is the individualgroup. The purpose of this research is to know the educational cooperation between Indonesiaand Singapore, the Sister School cooperation of SMA Labschool Jakarta with CHIJ St. Joseph'sConvent Singapore and also to see how the impact of that cooperation for the both of countries.This research shows that the education cooperation between Indonesia and Singaporehas positively impact for the cost of education and socio-culture of both countries. The samebenefits are also felt by the schools. However, in the implementation of this cooperation, bothIndonesia and Singapore also face a number of challenge. Therefore, Indonesiaand Singaporeare expected to improve a better educational cooperation so that it can also improve the imageof these countries in the world.Keywords: Sister School,Indonesia, Singapore, Cooperation, Impact